1991
DOI: 10.1093/jpepsy/16.3.307
|View full text |Cite
|
Sign up to set email alerts
|

Peer Relationships and Adjustment in Children with Cancer

Abstract: Evaluated the psychosocial adaptations of children with cancer (n = 24, ages 8-18) as compared with same classroom controls on indices of (a) peer- and self-perceptions of sociability, aggression, and social isolation; (b) overall popularity; (c) mutual friendships; (d) feelings of loneliness; and (e) self-concept in multiple domains. Although the peer report data showed that children with cancer had a social reputation as significantly more socially isolated, no significant differences were found for their po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
0
2

Year Published

1993
1993
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 89 publications
(56 citation statements)
references
References 0 publications
1
53
0
2
Order By: Relevance
“…Both patients had problems with body image, became extremely anxious about their health, and felt socially isolated from their peer groups-findings that have also been reported in adolescents with diabetes 25 and cancer. 26 Although there were no differences between mean scores for boys and girls pre-transplant, girls had higher scores after transplant, with the differences approaching statistical significance. One possible contributory factor is the effects of the drugs on physical appearance-a source of distress for many patients posttransplant, but particularly for girls.…”
Section: Discussionmentioning
confidence: 84%
“…Both patients had problems with body image, became extremely anxious about their health, and felt socially isolated from their peer groups-findings that have also been reported in adolescents with diabetes 25 and cancer. 26 Although there were no differences between mean scores for boys and girls pre-transplant, girls had higher scores after transplant, with the differences approaching statistical significance. One possible contributory factor is the effects of the drugs on physical appearance-a source of distress for many patients posttransplant, but particularly for girls.…”
Section: Discussionmentioning
confidence: 84%
“…Factor analysis of these roles has revealed 3 underlying constructs: 1) sociability/leadership (e.g., someone who is a good leader, somebody who has many friends), 2) aggressive/disruptive (e.g., a person who gets into fights a lot, somebody who picks on other children), and 3) sensitive/isolated (e.g., someone who is usually sad, someone who is often left out). Dimension scores of the RCP have been shown to be both internally consistent (peer ␣ values range from 0.81 to 0.95; teacher ␣ values range from 0.58 to 0.76; self ␣ values range from 0.71 to 0.99) and stable; RCP-peer correlations across a 17-month interval range from 0.63 to 0.65 (31,32,35). Peer nominations on the RCP correlate significantly with teacher (0.35-0.51) (31,36) and self (0.14-0.22) (37) nominations.…”
Section: Methodsmentioning
confidence: 96%
“…Dimension scores of the RCP have been shown to be both internally consistent (peer ␣ values range from 0.81 to 0.95; teacher ␣ values range from 0.58 to 0.76; self ␣ values range from 0.71 to 0.99) and stable; RCP-peer correlations across a 17-month interval range from 0.63 to 0.65 (31,32,35). Peer nominations on the RCP correlate significantly with teacher (0.35-0.51) (31,36) and self (0.14-0.22) (37) nominations. Moreover, in 1388 NOLL ET AL several longitudinal studies, the sociability/leadership score in childhood was shown to be predictive of later indices of competence, whereas the aggressive/disruptive and sensitive/ isolated scores were shown to be predictive of psychopathologic disorders and behavioral problems (38)(39)(40)(41).…”
Section: Methodsmentioning
confidence: 96%
See 2 more Smart Citations